Flying Parts : best practices in organisational innovation following implementation of new technologies - Kleinsmith, Niela, (SAGE business cases., 2018)
Flying Parts, a mid-sized European component parts manufacturer for the aerospace industry, implemented a range of new technologies in the early 2000's when it became a Tier 1 subcontractor. The implementation of these new technologies triggered an organisational transformation: jobs and roles were redefined, a team structure replaced a hierarchical one, selected lean principles were introduced to increase quality and productivity, and employees became directly implicated in problem-solving, decision-making and innovation. Although absent from the company prior to these innovations, union clubs were invited by employees and welcomed by management when these transformations occurred.